2019
DOI: 10.1371/journal.pntd.0007673
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional blood signatures for active and amphotericin B treated visceral leishmaniasis in India

Abstract: Amphotericin B provides improved therapy for visceral leishmaniasis (VL) caused by Leishmania donovani , with single dose liposomal-encapsulated Ambisome providing the best cure rates. The VL elimination program aims to reduce the incidence rate in the Indian subcontinent to <1/10,000 population/year. Ability to predict which asymptomatic individuals (e.g. anti-leishmanial IgG and/or Leishmania-specific modified Quantiferon positive) will progress to clinical VL would help in monitoring … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 66 publications
7
24
3
Order By: Relevance
“…They all bind to CXCR3 and play multiple roles in promoting T cell adhesion and in the chemoattraction of monocytes and macrophages, T cells, NK cells, and dendritic cells. In our study we also identified GBP1 (Fakiola et al, 2019) as one of 10 top genes induced in active compared to treated VL cases. This gene encodes the interferon-g-induced guanylate binding protein GBP1.…”
Section: A B Csupporting
confidence: 55%
See 3 more Smart Citations
“…They all bind to CXCR3 and play multiple roles in promoting T cell adhesion and in the chemoattraction of monocytes and macrophages, T cells, NK cells, and dendritic cells. In our study we also identified GBP1 (Fakiola et al, 2019) as one of 10 top genes induced in active compared to treated VL cases. This gene encodes the interferon-g-induced guanylate binding protein GBP1.…”
Section: A B Csupporting
confidence: 55%
“…For the first arm of this study we used chip-based transcriptomics to study expression profiles in whole blood from active VL cases, Amphotericin B treated VL cases, asymptomic individuals, and healthy unaffected endemic controls (Fakiola et al, 2019). Interestingly, no differentially expressed genes (DEGs) were identified when comparing a group of individuals who had asymptomatic infection as determined by high IgG or positive Quantiferon responses compared to healthy endemic controls who were negative by these assays (Figure 2A).…”
Section: Transcriptional Profiling Of Vlmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Sb v is still effective and commonly used for VL treatment in Sudan [ 88 ]. Currently, a single dose of liposomal amphotericin B (AmBisome) is an effective VL treatment option and recommended as the first line treatment in the elimination program on the Indian subcontinent [ 89 ]. However, the high cost of the drug limits access in endemic areas and can lead to underdosing and incomplete treatment conducive to the emergence of drug resistant strains [ 90 ].…”
Section: Introductionmentioning
confidence: 99%